Location-based technologies for supporting elderly pedestrian in “getting lost” events. - Pulido Herrera, Edith (Disability & Rehabilitation: Assistive Technology, 2017)
Purpose:Localization-based technologies promise to keep older adults with dementia safe and support them and their caregivers during getting lost events. This paper summarizes mainly technological contributions to support the target group in these events. Moreover, important aspects of the getting lost phenomenon such as its concept and ethical issues are also briefly addressed. Methods:Papers were selected from scientific databases and gray literature. Since the topic is still in its infancy, other terms were used to find contributions associated with getting lost e.g. wandering. Results:Trends of applying localization systems were identified as personal locators, perimeter systems and assistance systems. The first system barely considered the older adult’s opinion, while assistance systems may involve context awareness to improve the support for both the elderly and the caregiver. Since few studies report multidisciplinary work with a special focus on getting lost, there is not a strong evidence of the real efficiency of localization systems or guidelines to design systems for the target group. Conclusions:Further research about getting lost is required to obtain insights for developing customizable systems. Moreover, considering conditions of the older adult might increase the impact of developments that combine localization technologies and artificial intelligence techniques.Implications for RehabilitationWhilst there is no cure for dementia such as Alzheimer’s, it is feasible to take advantage of technological developments to somewhat diminish its negative impact. For instance, location-based systems may provide information to early diagnose the Alzheimer’s disease by assessing navigational impairments of older adults.Assessing the latest supportive technologies and methodologies may provide insights to adopt strategies to properly manage getting lost events.More user-centered designs will provide appropriate assistance to older adults. Namely, customizable systems could assist older adults in their daily walks with the aim to increase their self-confidence, independence and autonomy.